The lytB Gene of Escherichia coli Is Essential and Specifies a Product Needed for Isoprenoid Biosynthesis - McAteer, Sean (American Society for Microbiology, 2001)
LytB and GcpE, because they are codistributed with other pathway enzymes, have been predicted to catalyze unknown steps in the nonmevalonate pathway for isoprenoid biosynthesis. We constructed a conditional Escherichia coli lytB mutant and found that LytB is essential for survival and that depletion of LytB results in cell lysis, which is consistent with a role for this protein in isoprenoid biosynthesis. Alcohols which can be converted to pathway intermediates beyond the hypothesized LytB step(s) support limited growth of E. coli lytB mutants. An informatic analysis of protein structure suggested that GcpE is a globular protein of the TIM barrel class and that LytB is also a globular protein. Possible biochemical roles for LytB and GcpE are suggested.